Entre variabilité interannuelle et stratégies individuelles : effets des paramètres environnementaux sur l’écologie alimentaire et le succès reproducteur des éléphants de mer de l’archipel de Kerguelen - Mestre, Julie (Université Sorbonne, 2020)
Because time-series relative to foraging ecology, environmental parameters and population trends are scarce, few studies focused on the mechanisms linking oceanographic variables with the foraging behaviour and breeding success in marine top predators. This PhD thesis aims to assess the effects of inter-annual environmental conditions and individual strategies on the foraging ecology and breeding success of the southern elephant seal (Mirounga leonina), a key species of the Southern Ocean. The simultaneous analysis of stable isotopes and tracking-diving time-series highlighted that the foraging habitats, as well as the diving- and foraging behaviour of female seals, remained stable over the last fourteen years. This thesis also revealed a consistency in the utilization proportion of the Antarctic and sub-Antarctic foraging habitats. The body condition of female seals tend to improve less when they exploit the latter habitat, and the corresponding weaning mass of their pups, considered as a proxy of the breeding success, was globaly higher but tended to decrease over the study period. A difference in habitat quality was detected between the areas located east and west of the Kerguelen archipelago, with the area located west providing higher foraging and breeding success. Moreover, a structuration in foraging habitat and breeding success was highlighted between two colonies (i.e. breeding sites) located at Kerguelen Island. Despite consistency in the behaviour of female seals, an overall improvement in body condition was assessed over the study period. Combined with a global decrease in ä13C values, this result suggests that some modifications are occurring in the food webs of the Southern Ocean. En raison du manque de series temporelles associant ecologie en mer, parametres oceanographiques, et trajectoires demographiques, peu dfetudes se sont interessees aux mecanismes reliant conditions oceanographiques, succes alimentaire a lfechelle des trajets en mer, et succes reproducteur associe chez des predateurs ...